Security enhancement to autonomous vehicles networks - Truong, Thanh Thai (Nanyang Technological University, 2021)
Autonomous Vehicle Network technology is moving fast thanks to the rapid development of research in VANET technology. While the performance of recent communication technology can satisfy the huge requirements of VANET technology, the modern security frameworks are still not be able to protect VANETs from previous attacks from threat actors who might target this new industry. Over the last 20 years, multiple research have been conducted to develop the most secure and lightweight security frameworks for VANET. One of the most promising field is Intrusion Detection System in VANET, which utilizing the state-of-the-art detection algorithm including machine learning. On the other hand, there is none commercialized IDS framework for VANET, thus this raised the question if there are still room for improvement in IDS framework for VANET. This final year project will review the state-of-the-art intrusion detection system in VANET, investigate the possibility of improvement and propose solutions to this question.